Shaping prospective teachers' national values through mobile learning: An exploration of practice - Zhumabayeva, Aziya; Nurzhanova, Sazhila; Bazarbekova, Rabiga; Zhumabayeva, Zhazira; Stambekova, Assel (Journal of Education and e-Learning Research, 2025)
Comparative studies of national values are becoming increasingly important in contemporary globalization processes. An essential condition for shaping national values in learners is the enrichment of pedagogical technology with components of digital technology. Both qualitative and quantitative approaches were used in this study. This research aims to examine the efficacy of mobile learning in shaping the national values of prospective teachers. 180 participants participated in this study. Diagnostics of the levels of national values formation in the initial stage confirmed the assumption about the low formation of national values among teacher candidates and, consequently, the need for targeted work on their formation. This study demonstrates that significant advances in students' national values have occurred following the introduction and testing of mobile learning with EG participants to shape national values. This study serves as the basis for creating strategies for shaping the national values of learners in universities and as a methodological basis for adapting mobile learning for the shaping of national values.